Projeto Fénix: o que pensam os alunos sobre os fatores que promovem as suas aprendizagens? - Cabral, Ilídia (2017)
This article focuses on the perception of two groups of pupils with different academic performances regarding the factors that most influence their learning. We intend to know what these two groups value the most in such learning and whether there are differences in such perception. By means of an open questionnaire applied to 39 pupils of 16 schools from the Fénix network (“More School Success” program), stratified in two groups (pupils with good academic results and pupils with poor academic results), it has been possible to know their representations of the factors that make them learn the most. To read this production we used the good schools’ categorization by MacBeath (1999), and concluded that the dimensions (i) support to their learning, (ii) relations between pupils and between pupils and teachers, (iii) organization and communication, and (iv) value attributed to education are the most referred, which is aligned with the generality of the knowledge available. It can also be concluded that the dimensions with a more organizational nature, non-directly observable by pupils, tend not to be referred, especially by pupils with lower academic results. Last, we note that some implicit risks of a project that makes differentiation an educational surplus value, but that may contribute to the emergence of growing inequality between pupils.